Biogeochemical Control of the Coupled CO(2)–O(2) System of the Baltic Sea: A Review of the Results of Baltic-C - Omstedt, Anders (Springer Netherlands, 2014)
Past, present, and possible future changes in the Baltic Sea acid–base and oxygen balances were studied using different numerical experiments and a catchment–sea model system in several scenarios including business as usual, medium scenario, and the Baltic Sea Action Plan. New CO(2) partial pressure data provided guidance for improving the marine biogeochemical model. Continuous CO(2) and nutrient measurements with high temporal resolution helped disentangle the biogeochemical processes. These data and modeling indicate that traditional understandings of the nutrient availability–organic matter production relationship do not necessarily apply to the Baltic Sea. Modeling indicates that increased nutrient loads will not inhibit future Baltic Sea acidification; instead, increased mineralization and biological production will amplify the seasonal surface pH cycle. The direction and magnitude of future pH changes are mainly controlled by atmospheric CO(2) concentration. Apart from decreasing pH, we project a decreasing calcium carbonate saturation state and increasing hypoxic area.